The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.joto.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Tophaceous gout of the middle ear

Abstract: We present a very rare case of tophaceous gout of the middle ear causing conductive hearing loss, with special emphasis on Computed Tomography presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 9 publications
(13 reference statements)
0
14
0
Order By: Relevance
“…The sex ratio was 1/1 and the pathology is more frequent for patients over 55-years-old. The major clinical symptom was a simple progressive hearing loss ( Gargula et al., 2019 ). Abnormal otoscopy occurred in 7 out of 8 patients ( Mutlu et al., 2016 ) with 50% of white sclerotic plaque under the normal tympanic membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The sex ratio was 1/1 and the pathology is more frequent for patients over 55-years-old. The major clinical symptom was a simple progressive hearing loss ( Gargula et al., 2019 ). Abnormal otoscopy occurred in 7 out of 8 patients ( Mutlu et al., 2016 ) with 50% of white sclerotic plaque under the normal tympanic membrane.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Although conductive hearing loss due to a middle ear mass is common, a tophus in the middle ear is an uncommon cause of a middle ear mass. [3][4][5][6][7][8] The low incidence combined with the absence of clinical manifestations of gout or hyperuricemia in all known cases, including in this patient, explains why tophaceous gout in the middle ear is often misidentified as osteoma, cholesteatoma, or tympanosclerosis. 3,6,7 This emphasizes the importance of considering the diagnosis of a tophus in patients with conductive hearing loss and a mass in the middle ear.…”
Section: Discussionmentioning
confidence: 99%
“…PTA revealed a right CHL with a 50 dB ABG, High-resolution CT on right temporal bone revealed calcified mass at the anterior part of the tympanic cleft. Pathological examination of excised mass revealed gouty tophi in ME [20] . According to V.N.G test battery results, Dix-Hallpike test revealed that 9 subjects [22.5%] in the study group presented with peripheral vertigo [BPPV], this percentage was in agreement with Lin et al [9] ; they found 21% of total number of cases of BPPV to have hyperuricemia.…”
Section: Discussionmentioning
confidence: 99%
“…I-Spontaneous nystagmus: Subject was asked to sit with head upright and the back is supported, spontaneous nystagmus observed in complete absence of any visual fixation. Minimum observation period is 30 seconds.II-Gaze test: Subject was asked to fix his vision on the light bar, 20-degree eccentric position vertical and horizontal and the eye is kept in position for20-30 seconds. III-Oculomotor tests: Subject was seated on test chair 1.5 meters from the center of the T.V.…”
mentioning
confidence: 99%